2023
DOI: 10.3390/vetsci10010052
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vegan Diets on Indicators of Health in Dogs and Cats: A Systematic Review

Abstract: There has been an increase in vegetarianism and veganism in human populations. This trend also appears to be occurring in companion animals, with guardians preferring to feed their animals in accordance with their own dietary values and choices. However, there has been controversy amongst vets and online commentators about the safety of feeding vegan diets to carnivorous species, such as cats and dogs. In spite of this controversy, to date there has been no systematic evaluation of the evidence on this topic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, a sizeable and rapidly-growing body of evidence has now shown that both dogs and cats can thrive on nutritionally-sound vegan diets. Such results are evident within both canine (nine studies: [16][17][18][19][20][21][22][23][24]) and feline (four studies: [23,[25][26][27]) studies of health outcomes. Furthermore, their behavioural needs and welfare are not compromised by such diets [28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a sizeable and rapidly-growing body of evidence has now shown that both dogs and cats can thrive on nutritionally-sound vegan diets. Such results are evident within both canine (nine studies: [16][17][18][19][20][21][22][23][24]) and feline (four studies: [23,[25][26][27]) studies of health outcomes. Furthermore, their behavioural needs and welfare are not compromised by such diets [28].…”
Section: Discussionmentioning
confidence: 98%
“…A considerable body of recent evidence indicates that provided such diets are formulated to be nutritionally-sound, as modern commercial vegan diets usually are [15], dogs and cats maintained on vegan diets can have longevity and health at least equivalent, and in some respects superior, to those maintained on conventional meat-based diets. Such results are evident within studies of health outcomes in both dogs (nine studies: [16][17][18][19][20][21][22][23][24]) and cats (four studies: [23,[25][26][27]). Dietary palatability also appears equivalent overall [28].…”
Section: -mentioning
confidence: 97%
“…Regarding health and palatability, while there are numerous methodological limitations with the existing literature, the latest systematic review found that plant-based pet foods are comparable, or perhaps slightly more advantageous, for the health of pet dogs and cats (Domínguez-Oliva et al, 2023). However, a cautious approach is warranted, as further validation and controlled clinical trials are required (Davies, 2022).…”
Section: Pet Food: Environmental Impacts Of Insects Compared To Conve...mentioning
confidence: 99%
“…Dietary sources serve as pathways through which pets obtain nutrients, and understanding the availability of vitamin A in various diets is crucial for ensuring optimal pet health [10,11]. The decisions about pet diets are not just about providing food; they are intentional choices that significantly impact the pets' wellness by shaping their nutritional needs [12,13]. Vitamin A, sourced from various foods, becomes a critical consideration, whether obtained from animal products or as a precursor from plant-based sources.…”
Section: Introductionmentioning
confidence: 99%